KETERLIBATAN PEREMPUAN DALAM PENYUSUNAN PRODUK HUKUM DAERAH DI KABUPATEN BANYUMAS - Ardhanariswari, Riris; Marwah, Sofa; Sudrajat, Tedi (Faculty of Law, Universitas Jenderal Soedirman, 2008)
Solution of Raperda in regional parliament has entangled governmental element, parliament and society. Involvement of society assessed before existence of formal solution of Raperda is at hearing public process and empirical facts analysis by SKPD. When solution of Raperda, society can follow to involve actively at level I, II and of IV in plenary meeting. Besides that, after perda have done, society still enabled to involve in public test. In this case, legal status between woman and men is same. The women's involvement in making of regional law, especially in Banyumas, still experience of various constraint. In this case, role of woman (generally) still assumed lower or not yet maximal. Opportunity have been given by government but woman still not yet earned the rights maximally. There are role of woman in attendance but role in input form is not yet maximal. In general, arising out constraint to women involvement in making regional law is come from society mindset concerning woman, cultural and quality of the Human Resources. Kata Kunci : Keterlibatan Perempuan, Produk Hukum Daerah